A Novel Variant in the TBC1D24 Lipid-Binding Pocket Causes Autosomal Dominant Hearing Loss: Evidence for a Genotype-Phenotype Correlation - Parzefall, Thomas; Frohne, Alexandra; Koenighofer, Martin; Neesen, Juergen; Laccone, Franco; Eckl-Dorna, Julia; Waters, Jonathan J.; Schreiner, Markus; Amr, Sami Samir; Ashton, Emma; Schoefer, Christian; Gstœttner, Wolfgang; et al. (Frontiers in Cellular Neuroscience, 2020)
Background: Hereditary hearing loss is a disorder with high genetic and allelic heterogeneity. Diagnostic screening of candidate genes commonly yields novel variants of unknown clinical significance. TBC1D24 is a pleiotropic gene associated with recessive DOORS syndrome, epileptic encephalopathy, myoclonic epilepsy and both recessive and dominant hearing impairment. Genotype-phenotype correlations have not been established to date but could facilitate diagnostic variant assessment and elucidation of pathomechanisms. Methods and Results: Whole-exome and gene panel screening identified a novel (c.919A>C; p.Asn307His) causative variant in TBC1D24 in two unrelated Caucasian families with autosomal dominant nonsyndromic late-onset hearing loss. Protein modelling on the Drosophila TBC1D24 ortholog Skywalker crystal structure showed close interhelix proximity (6.8Å) between the highly conserved residue p.Asn307 in alpha-18 and the position of the single known pathogenic dominant variation (p.Ser178Leu) in alpha-11 that causes a form of deafness with similar clinical characteristics. Conclusion: Genetic variants affecting two polar hydrophilic residues in neighboring helices of TBC1D24 cause autosomal dominant nonsyndromic late-onset hearing loss. The spatial proximity of the affected residues suggests the first genotype-phenotype association in TBC1D24-related disorders. Three conserved residues in alpha-18 contribute to the formation of a functionally relevant cationic phosphoinositide binding pocket that regulates synaptic vesicle trafficking which may be involved in the molecular mechanism of disease.